2005
DOI: 10.1161/01.str.0000160749.61763.95
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of the Performance, Reporting, and Interpretation of Studies Comparing Carotid Plaque Imaging With Histology

Abstract: Background and Purpose-Carotid plaque instability is an important determinant of stroke risk. There are now a number of different imaging techniques that provide information on carotid plaque morphology. However, it is unclear how they compare with one another or whether they can reliably assess plaque instability. Studies comparing imaging with pathology have shown highly variable results, even for similar imaging techniques. This may be because of variable pathology techniques rather than differences in imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 104 publications
3
61
0
2
Order By: Relevance
“…Because of that, several errors are introduced both in the removal and the preparation of the plaque and in the direction of the section under analysis. Lovett et al 13 suggested that the histological study of atheromas should be standardized. In this study, attempts were made to minimize these errors by removing the plaque with as minimal rupture as possible and using the image of the histological slide as the standard reference, choosing the area on the ultrasound image that had the same relation between the lumen and the wall, and studying a section of this region instead of the entire plaque.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of that, several errors are introduced both in the removal and the preparation of the plaque and in the direction of the section under analysis. Lovett et al 13 suggested that the histological study of atheromas should be standardized. In this study, attempts were made to minimize these errors by removing the plaque with as minimal rupture as possible and using the image of the histological slide as the standard reference, choosing the area on the ultrasound image that had the same relation between the lumen and the wall, and studying a section of this region instead of the entire plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Other complementary imaging tests, such as positron emission tomography (PET) and single photon emission CT (SPECT), may play an adjuvant role in follow-up. However, although promising, they are expensive, and access to them is limited 2,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The most commonly used method of MR plaque imaging consists of a series of images with different contrast weightings. In this 'multi-contrast' protocol (Figure 1 20 In recent years, many studies have investigated the association between MRI plaque characteristics and subsequent cerebrovascular events. IPH in particular is thought to be a crucial parameter related to plaque rupture and therefore studied extensively.…”
Section: Detection Of Embolic Signals With Transcranial Doppler (Tcd)mentioning
confidence: 99%
“…In addition, irregularities of the carotid plaque surface may represent a good marker of its vulnerability, which translates into increased risk of thromboembolic cerebral events [11][12][13]. With regards to plaque echogenicity, several studies clearly showed that echolucent carotid plaques were more related to cardiovascular events (CVEs) than were echogenic ones [14][15][16]: in fact, echolucent plaques histologically demonstrate a higher lipid content and a reduced fibrous and calcium content, which represent important features of advanced and/or unstable atherosclerotic disease [17]. Different methods exist for the quantitative assessment of the ultrasonographic properties of Among healthy adults aged 20 to 79 years, risk scores classify 75% of the subjects as low or intermediate risk, but in these categories a substantial number of CVEs (about 60%) occurs [31].…”
mentioning
confidence: 99%